Extended MR with Nesting of Predicate Expressions as a Basic Logic for Social Phenomena - Parol, Aleksander; Pietrowicz, Krzysztof; Szalacha-Jarmużek, Joanna (Bulletin of the Section of Logic, 2021)
In this article, we present the positional logic that is suitable for the formalization of reasoning about social phenomena. It is the effect of extending the Minimal Realisation (MR) logic with new expressions. These expressions allow, inter alia, to consider different points of view of social entities (humanistic coefficient). In the article, we perform a metalogical analysis of this logic. Finally, we present some simple examples of its application.